Number and Density of AMPA Receptors in Individual Synapses in the Rat Cerebellum as Revealed by SDS-Digested Freeze-Fracture Replica Labeling - Masugi-Tokita, Miwako (J Neurosci, 2007)
The number of AMPA receptor (AMPAR) is the major determinant of synaptic strength at glutamatergic synapses, but little is known about the absolute number and density of AMPARs in individual synapses. Using SDS-digested freeze-fracture replica labeling, which has high detection efficiency comparable with electrophysiological noise analysis for functional AMPAR, we analyzed three kinds of excitatory synapses in the molecular layer of the adult rat cerebellum. In parallel fiber (PF)–Purkinje cell (PC) synapses, we found large variability in the number (38.1 ± 34.4 particles per synapse, mean ± SD; range, 2–178 particles per synapse) and density (437 ± 277 particles/μm(2); range, 48–1210 particles/μm(2)) of immunogold-labeled AMPARs. Two-dimensional view and high sensitivity of this method revealed irregular-shaped small AMPAR clusters within synapses. Climbing fiber (CF)–PC synapses had higher number of AMPAR labeling (68.6 ± 34.5 particles per synapse) than PF–PC and PF–interneuron synapses (36.8 ± 14.4 particles per synapse). Furthermore, AMPAR density at CF–PC and PF–interneuron synapses was approximately five times higher and more uniform than that at PF–PC synapses. These results suggest input- and target-dependent regulation of AMPAR-mediated synaptic strength.